2023
DOI: 10.3389/fvets.2023.1245790
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microalgae as dietary supplement on palatability, digestibility, fecal metabolites, and microbiota in healthy dogs

Ana R. J. Cabrita,
Joana Guilherme-Fernandes,
Maria Spínola
et al.

Abstract: The current trend of dog owners increasingly favoring the functional value of food to assure preventive health and wellbeing of their pets has been raising the interest in microalgae as natural additives with bioactive properties. However, scientific studies addressing the effects of microalgae supplementation in diets for dogs are scarce. This study aimed to evaluate the effects of dietary supplementation with three microalgae species (Chlorella vulgaris, Nannochloropsis oceanica, and Tetradesmus obliquus) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 107 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…Indeed, earlier studies found no negative or even positive effects on palatability with higher inclusion levels of marine by-products than the level used in the current study ( 12 , 95 ). The lower palatability of diets with 15% inclusion of squid meal or shrimp hydrolysate might be due to protein sources being mixed with the basal diet immediately before being offered to dogs, instead of included in the kibble, as previously shown with microalgae supplementation ( 11 ). Future research should be performed to evaluate the palatability of diets containing squid meal and shrimp hydrolysate included in the extruded complete diet.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Indeed, earlier studies found no negative or even positive effects on palatability with higher inclusion levels of marine by-products than the level used in the current study ( 12 , 95 ). The lower palatability of diets with 15% inclusion of squid meal or shrimp hydrolysate might be due to protein sources being mixed with the basal diet immediately before being offered to dogs, instead of included in the kibble, as previously shown with microalgae supplementation ( 11 ). Future research should be performed to evaluate the palatability of diets containing squid meal and shrimp hydrolysate included in the extruded complete diet.…”
Section: Discussionmentioning
confidence: 95%
“…The method of total fecal collection was used to assess the apparent total tract digestibility (ATTD) of the basal and experimental diets. The in vivo ATTD of the basal diet was determined previously to experiments 1 and 2, using 12 animals for 10 days (5 days for adaptation and 5 days for feces collection), as recommended by FEDIAF and earlier described ( 11 ). The two digestibility trials performed to evaluate the effects of inclusion levels of squid meal and shrimp hydrolysate were designed according to a replicated Latin square 3 × 3, with six animals (three males and three females, from the 12 animals used for the determination of the in vivo digestibility of the basal diet), three experimental periods of 10 days (5 days for adaptation to the diet and 5 days for total feces collection) and three dietary inclusion levels (50, 100 or 150 g kg −1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Feces were thawed, and pH was determined using a potentiometer (pH and Ion-Meter GLP 22, Crison, Barcelona, Spain). Ammonia-N concentration was determined according to the method of Smith and Murphy ( 47 ) adapted to dog feces as described by Cabrita, Guilherme-Fernandes ( 48 ). Briefly, 1 g of feces were solubilized in 10 mL of KCl 2 M, centrifuged for 60 min at 5200 × g at 4°C, and the supernatant filtered using a 0.45 μm pore size polyethersulfone syringe filter (FILTER-LAB, Barcelona, Spain).…”
Section: Methodsmentioning
confidence: 99%